Rebound effect on Charged Based Bio-TFETs for different biomolecules - Macambira, C. N.; Agopian, P. G. D. [UNESP]; Martino, J. A.; IEEE (Ieee, 2019)
In this work, the charged biomolecules with different permittivity (epsilon) localized on the drain underlap region of a double gate (DG) N-type tunneling field effect transistor (nTFET) for biosensing purpose (Bio-TFET) is presented. The fixed charges are localized at the interface between the biomaterial and the silicon channel. The main studied parameter of the charged Bio-TFET is the sensitivity. In the charge range studied, the results show that the device presents higher sensitivity for lower dielectric constant biomolecules (e.g., thiol linkers and biotin) and it was also observed a rebound effect on the drain current (and sensitivity) for high concentration ( > 1x10(12) cm(-2)) of positive fixed charges. This rebound effect is caused by the shift of the electric field peak from the drain/channel to the gate/biomaterial regions.
Keywords: TFET; Biosensor; Bio-TFET; Permittivity; Charge; Sensitivity; Rebound